Stability of silver colloids and catalytic activity of CTAB-capped phosphorous and boron doped gold nanoparticles supported on carbon black as a dispersed electrocatalyst for ethanol oxidation reaction - Eng, Jessel Jie Khiang (2017)
This report focuses on the study of the stability of Silver colloids using UV/vis spectrometry. A control experiment involving Silver and its solvents was carried out, followed by experiments involving dried Silver powder which was redispersed in DI water and PVP solution respectively. Redispersing PVP-capped silver powder in DI water proved to provide better colloidal stability. Electrochemical studies were carried out to investigate the role of Boron and Phosphorous in the catalytic activity and stability of gold nanoparticles. Cyclic Voltammetry was applied to measure the specific activity of the catalysts while chronoamperometry was carried out to measure current and stability of the catalysts. After which, hexadecyltrimethylammonium bromide (CTAB), a capping agent, was introduced into the Boron and Phosphorous doped Gold catalyst. It was found that CTAB, with the right amount, greatly enhances the colloidal stability of the eventually spherical Gold nanoparticles. Cyclic Voltammetry was applied to measure the specific activity of CTAB-capped Gold catalyst. It was found that CTAB-capped Gold catalyst exhibits much higher specific activity than its CTAB-less counterpart.